Singapore Airlines’ strategy in being named the world’s best airline 2023 by SKYTRAX - Krissanabhat Boonchuay, Jongkolgorn Singhto, Naradom Oxsu; Sasiporn Dilokdamkeng (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2025)
This article studied Singapore Airlines’ strategy in being named the world’s best airline 2023 by Skytrax, the international air transport rating organization providing quality audit, rating and quality certification to airlines and airports across the world, based in the United Kingdom. The objectives of the study were to investigate marketing policy and strategy of Singapore Airlines in being named the world’s best airline 2023 including factors of success and sustainability of Singapore Airlines that it is not only the national airline of Singapore but the symbol of the pride and excellence in services of Asian airlines. Its success is guaranteed by 4 awards, i.e. World’s Best Airline, Best First Class Airline, Best First Class Comfort Amenities, and Best Airline in Asia. It is a part of the Star Alliance network, covering 1,250 destinations in 195 countries. The study result leads to the development of appropriate management model for airline business and an increase in competitive advantage in aviation industry that seems to be more challenging at present for achieving excellence in a sustainable manner.